Faktor-faktor yang mempengaruhi nilai perusahaan pada perusahaan property dan real estate di bursa efek indonesia - Wijoyo, Amin (Jurnal Ekonomi, 2018)
The purpose of this study is to test and to analyze the association of asset structure, profitability, debt policy, dividend policy either partially or simultaneously, to compnay value of property and real estate firm that listed at Indonesian Stock Exchange in the period of 2014-2016. The method used is multiple regression analysis using SPSS 23. The result show that asset structure, profitability, debt policy, dividend policy have a simultaneous influence with company value. Meanwhile, partially only profitability have a influence with company value. Asset structure, debt policy, and dividend policy not have a influence with company value.